Web-based energy monitoring and control system - Mohd Radzi, Mohd Amran; Mariun, Norman; Mohd Noor, Samsul Bahari; Mahmod, Senan; Md. Jim, Abd. Razak (2002)
Recently, there is a continuous increasing of the energy demand. This scenario has caused the supply capacity need to be added and of course, the cost will increase. One of the ways to solve this problem is by introducing energy management. Through this approach, a computerized energy management, Energy Management and Control System (EMCS) is developed as a method to conserve and managing the energy used in commercial, industrial and large residential complexes. At the same time, the increasing use of Internet application and web-based system has caused this system to be developed for being connected to the Internet. Therefore, this paper will explain the process of design and development of software that could be used as an on-line energy monitoring and control system through the web. By using this software, the measurement data from the loads was acquired through monitoring process. To implement energy saving program totally, the system would allow the user to control manually or automatically.